EFFECTIVENESS OF INTRALESIONAL CORTICOSTEROID INJECTION FOR NODULOCYSTIC ACNE : A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS AND PRIMARY STUDIES - Rielyana Lumban Gaol (The International Journal of Medical Science and Health Research, 2026)
Introduction: Nodulocystic acne represents the most severe phenotype of acne vulgaris, associated with significant physical and psychosocial morbidity. Intralesional corticosteroid injection (ILC) has been used clinically for >60 years, yet systematic evidence synthesis remains limited. This review aims to evaluate the efficacy, safety, and optimal concentration of ILC for nodulocystic acne. Methods: Systematic review conducted according to PRISMA 2020 guidelines. Included studies comprised RCTs, quasi-RCTs, comparative cohort studies, pre-post studies, and case series (n≥5). Risk of bias was assessed using Cochrane RoB 2.0 and Newcastle-Ottawa Scale. Results: Fifteen studies comprising 1,247 subjects were included. Triamcinolone acetonide (TA) at concentrations of 0.63–5 mg/mL demonstrated consistent efficacy, with symptomatic improvement onset within 24–72 hours and median lesion resolution of 4.6–8.1 days depending on modality. Lesion diameter reduction reached 65–85% by Day 7. Mean VAS pain score reduction was 2.27 points (p<0.0001) with cryoanesthesia. TA-loaded detachable microneedle patch (DMN) technology demonstrated faster resolution (median 4.6 vs 8.1 days; p<0.05). Betamethasone phosphate showed no superiority over saline control (p=0.16). Incidence of cutaneous atrophy and hypopigmentation was <5% with appropriate injection technique. Discussion: TA at 0.63–2.5 mg/mL constitutes the most effective and safe ILC agent. Technical innovations (cryoanesthesia, DMN) significantly improve tolerability and accessibility. Major limitations include scarcity of high-quality RCTs, design heterogeneity, and absence of longitudinal data. Conclusion: Intralesional triamcinolone acetonide injection at 0.63–2.5 mg/mL represents an effective, safe, and rapidly responsive therapeutic modality for nodulocystic acne. Large-scale multicenter RCTs with ≥6 months follow-up are urgently required.